2022
DOI: 10.3390/ijms23116205
|View full text |Cite
|
Sign up to set email alerts
|

AMPK and the Challenge of Treating Hypoxic Pulmonary Hypertension

Abstract: Hypoxic pulmonary hypertension (HPH) is characterized by sustained elevation of pulmonary artery pressure produced by vasoconstriction and hyperproliferative remodeling of the pulmonary artery and subsequent right ventricular hypertrophy (RVH). The search for therapeutic targets for cardiovascular pathophysiology has extended in many directions. However, studies focused on mitigating high-altitude pulmonary hypertension (HAPH) have been rare. Because AMP-activated protein kinase (AMPK) is involved in cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 255 publications
0
4
0
Order By: Relevance
“…AMPK was a critical regulator of various biological processes, including cell growth, proliferation, autophagy and metabolism. Previous studies demonstrated the involvement of AMPK in the abnormal proliferation of PASMCs during PAH development [45,46].…”
Section: Discussionmentioning
confidence: 97%
“…AMPK was a critical regulator of various biological processes, including cell growth, proliferation, autophagy and metabolism. Previous studies demonstrated the involvement of AMPK in the abnormal proliferation of PASMCs during PAH development [45,46].…”
Section: Discussionmentioning
confidence: 97%
“…The combination of all drugs strengthens lung qi and warms Yang qi, causing blood stasis to dispel phlegm. Hypoxic pulmonary hypertension (HPH) is a long-term rise in pulmonary artery pressure caused by constriction of blood vessels and vascular reformation of the pulmonary arteries [12]. Pulmonary vascular remodeling is defined by thickening of the pulmonary artery media.…”
Section: Discussionmentioning
confidence: 99%
“…The oxidative stress response may damage blood vessels, undermine endovascular homeostasis, increase cellular Ca 2+ concentrations, and result in the degradation of proteins, lipids, and DNA [ 8 , 9 ]. During hypoxia, superoxide anions formed in the body alleviate NO-mediated vasodilation by producing peroxynitrites [ 10 , 11 ]. Thus, treatment of antioxidant stress has potential for the treatment of HAPH.…”
Section: Introductionmentioning
confidence: 99%